Effect of mechanical alloying and Ti addition on solution and ageing treatment of an AA7050 aluminium alloy - Kátia Regina Cardoso; Dilermando Nagle Travessa; Asunción García Escorial; Marcela Lieblich (Materials Research, 2007)
In this work, solution heat treatments at different temperatures were performed in a commercial based AA7050 aluminium alloy, with and without titanium addition, produced by mechanical alloying and hot extrusion with the aim to investigate the effect of titanium addition and mechanical alloying in the precipitates stability. The same heat treatment conditions were used in a reference sample obtained from a commercial AA7050 alloy. Solution heat treated samples were characterised by differential scanning calorimetry (DSC), optical microscopy and hardness test. Once the better temperature for the solution treatment of modified alloys was defined, the ageing curve at 120 °C was obtained to verify the effect of milling and Ti addition in the precipitation and in the maximum values of hardness obtained for the alloys.